2020
DOI: 10.1111/medu.14183
|View full text |Cite
|
Sign up to set email alerts
|

How to conceptualise self‐regulated learning: Implications for measurement

Abstract: When is self‐regulated learning not entirely self‐regulated? The authors argue SRL is socially embedded and we need better measurement of its reciprocal relationship with co‐regulated learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Overall, our findings confirm the importance of relationships and interactions in co-regulatory networks for medical students’ SRL in clinical settings. By elucidating the scope of co-regulation in clinical workplaces, this study builds on, contributes to, and reinforces changing conceptualizations of SRL as socially embedded learning activities [ 11 , 23 ]. Medical education research into SRL has shown that formulating learning goals in clinical settings requires learners and engaged supervisors to interact and negotiate for goals to be realistic and achievable [ 28 30 ], as well as to monitor performance [ 31 ].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Overall, our findings confirm the importance of relationships and interactions in co-regulatory networks for medical students’ SRL in clinical settings. By elucidating the scope of co-regulation in clinical workplaces, this study builds on, contributes to, and reinforces changing conceptualizations of SRL as socially embedded learning activities [ 11 , 23 ]. Medical education research into SRL has shown that formulating learning goals in clinical settings requires learners and engaged supervisors to interact and negotiate for goals to be realistic and achievable [ 28 30 ], as well as to monitor performance [ 31 ].…”
Section: Discussionmentioning
confidence: 91%
“…Students may have varied in understanding questionnaire items or might not have been able to assess themselves or their networks accurately. However, self-reports are commonly used to study both SRL [ 22 , 23 ] and networks [ 12 , 14 , 17 ]. Third, we focused on student-initiated interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the influence of self-regulation on learning has also been explored. Self-regulated learning builds on the concept of metacognition and also considers the influence of social and motivational factors on learning [42]. Self-regulated learning is generally described as a cyclical process, often triggered by the formulating of goals and the subsequent employment of strategies to achieve, and monitor advancement towards those goals, followed by engagement in reflection and the formulation of new learning goals.…”
Section: Exploring Student Academic Success Factorsmentioning
confidence: 99%
“…Por ello, debido a la complejidad de este constructo se hace necesario especificar qué variable y/o proceso es el que se desea analizar con tal de utilizar instrumentos que permitan medir de forma válida y fiable la variable en estudio (Streiner, Norman y Cairney, 2015). Además, es necesario comprender conceptualmente la variable que se desea medir respecto de ARA (Bransen y Govaerts, 2020).…”
Section: Introductionunclassified